Literature Review: Control and Reduction of Ethyl Carbamate Formation in Fermented Products - Pawestri, Setyaning; Syahbanu, Fathma (Agros Journal of Agriculture Science, 2023)
Ethyl carbamate (EC) can be found in fermented products and alcoholic beverages. Tests on animals show this compound is a multisite carcinogen. The International Agency for Research on Cancer (IARC) classifies ethyl carbamate as a group 2A carcinogen. Due to its toxicity, ethyl carbamate in food products can be hazardous to health. Ethyl carbamate can be formed during fermentation and storage, which involves the reaction between ethanol and carbamyl compounds. The main precursor for the formation of ethyl carbamate is arginine metabolism by Saccharomyces cerevisiae and other lactic acid bacteria. Considering the toxicity of ethyl carbamate, it is crucial to understand the formation pathway, prominent analytical and monitoring techniques, mitigation practices and experimental methods to reduce EC. An effort can be conducted to mitigate EC by modifying bacterial genes for fermentation, which can be an applicable solution for the food industry.